2017
DOI: 10.1142/s0219199716500115
|View full text |Cite
|
Sign up to set email alerts
|

Conformal semi-invariant submersions

Abstract: As a generalization of semi-invariant submersions, we introduce conformal semi-invariant submersions from almost Hermitian manifolds onto Riemannian manifolds. We give examples, investigate the geometry of foliations which arise from the definition of a conformal submersion and show that there are certain product structures on the total space of a conformal semi-invariant submersion. Moreover, we also check the harmonicity of such submersions and find necessary and sufficient conditions of a conformal semi-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…As a generalization of holomorphic submersions, the notion of conformal holomorphic submersions were defined by Gudmundsson and Wood [19]. In 2017, Akyol and Şahin [7] defined a conformal semi-invariant submersion from an almost Hermitian manifolds onto a Riemannian manifold. (For conformal submersions see also [6], [8]).…”
Section: Mmentioning
confidence: 99%
“…As a generalization of holomorphic submersions, the notion of conformal holomorphic submersions were defined by Gudmundsson and Wood [19]. In 2017, Akyol and Şahin [7] defined a conformal semi-invariant submersion from an almost Hermitian manifolds onto a Riemannian manifold. (For conformal submersions see also [6], [8]).…”
Section: Mmentioning
confidence: 99%
“…Recently, we introduced conformal anti-invariant submersions [20] and conformal semiinvariant submersions [21] from almost Hermitian manifolds, and gave examples and investigated the geometry of such submersions (see also [22,23]). We showed that the geometry of such submersions is different from their counterpart anti-invariant Riemannian submersions and semi-invariant Riemannian submersions.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, he also defined slant submersions from almost Hermitian manifolds in [41]. After that, many geometers studied this area and obtained lots of results on the new topic (see [3,4,6,13,21,25,26,36,38,[44][45][46]). Recent developments on the notion of Riemannian submersion can be found in [43].…”
Section: Introductionmentioning
confidence: 99%